Moving beyond informal action: sustainable energy and the humanitarian response system - Peter James Matthew Thomas; Sarah Rosenberg-Jansen; Aimee Jenks (Journal of International Humanitarian Action, 2021)
Abstract Energy and humanitarian action have long been uneasy bedfellows. In the field, many humanitarian practitioners lack the time or remit to engage with a complex issue such as energy, and the topic to date has received relatively little attention from the private, development and academic sectors. This paper hopes to provide more clarity on energy in forced displacement settings by analysing how energy is interwoven with the humanitarian cluster system. This paper has two aims: (1) to assess existing evidence in the sector and explain the links between energy and each of the humanitarian clusters and (2) to provide recommendations on how humanitarian response efforts can transition from informal action to a comprehensive response on sustainable energy provision. This paper is the first to investigate the role of energy using the cluster system as a framework and contributes to a rapidly evolving field of research and practice on energy in humanitarian contexts. Our analysis demonstrates that energy is not fully integrated within humanitarian programme planning. Further, it highlights pathways for improving humanitarian outcomes enabled by improved energy practices. We identify ten ways clusters can integrate action on energy to support crisis-affected communities.